2020
DOI: 10.3389/fcimb.2020.573097
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Histoplasma capsulatum Behavior on Zinc Deprivation

Abstract: Histoplasma capsulatum is a thermodimorphic fungus that causes histoplasmosis, a mycosis of global incidence. The disease is prevalent in temperate and tropical regions such as North America, South America, Europe, and Asia. It is known that during infection macrophages restrict Zn availability to H. capsulatum as a microbicidal mechanism. In this way the present work aimed to study the response of H. capsulatum to zinc deprivation. In silico analyses showed that H. capsulatum has eight genes related to zinc h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 58 publications
(84 reference statements)
1
17
0
Order By: Relevance
“…Interestingly, metabolic profile showed that glycolysis of glucose (fructose-6-phosphate) induces the biosynthesis of glycan and chitin in the cell wall. These results suggest that low metal availability increases the chitin and glycan content in fungal cell wall (Assuncao et al, 2020) a mechanism that has not been shown in yeast and other fungi (North et al, 2012;Wang et al, 2018). Data from the study also suggested that Zn 2þ restriction could trigger oxidative stress, a mechanism shown to be involved in excess Zn 2þ toxicity in yeast.…”
Section: Zn 2þ Uptake and Compartmentalisationmentioning
confidence: 61%
See 1 more Smart Citation
“…Interestingly, metabolic profile showed that glycolysis of glucose (fructose-6-phosphate) induces the biosynthesis of glycan and chitin in the cell wall. These results suggest that low metal availability increases the chitin and glycan content in fungal cell wall (Assuncao et al, 2020) a mechanism that has not been shown in yeast and other fungi (North et al, 2012;Wang et al, 2018). Data from the study also suggested that Zn 2þ restriction could trigger oxidative stress, a mechanism shown to be involved in excess Zn 2þ toxicity in yeast.…”
Section: Zn 2þ Uptake and Compartmentalisationmentioning
confidence: 61%
“…The genes included the transcription factor, Zap1 and members of CDF and ZIP family transporters. The transcriptional levels of ZRT1, ZRT2 and ZAP1 were induced in Zn 2þ depleted environment (Assuncao et al, 2020). Proteomics analysis of cells grown in Zn 2þ depleted environment at 24 h and 48 h showed 265 differentially expressed proteins.…”
Section: Zn 2þ Uptake and Compartmentalisationmentioning
confidence: 99%
“…To evaluate the sensitivity of the fungus P. brasiliensis to limiting zinc conditions, the growth and cell viability of yeast cells in zinc scarcity were evaluated. The results showed that zinc scarcity imposed by up to 200 µM DTPA did not significantly affect fungal viability, as shown in the dimorphic pathogenic fungus Histoplasma capsulatum [ 65 ]. Thus, P. brasiliensis harbors efficient mechanisms to support survival and growth in a Zn-limiting condition.…”
Section: Discussionmentioning
confidence: 99%
“…The host environment can also influence the chitin cell wall content, as shown recently for Histoplasma spp. [ 47 ]. Here Assunção et al demonstrate that low zinc availability in macrophages increases the chitin and glycan content in fungal cell wall.…”
Section: Pathogen-associated Molecular Patternsmentioning
confidence: 99%
“…The host environment can also influence the chitin cell wall content, as shown recently for Histoplasma spp. [47].…”
Section: Pathogen-associated Molecular Patterns 41 Chitinmentioning
confidence: 99%